'Slipping through the Net': The Impact of Incremental Development on the Built Environment of the Historic Coastal Town of Queenscliff in Victoria, Australia. (1st January 2018) - de Jong, Ursula; Fuller, Robert; Beynon, David; Winkler, Sally
Abstract: Studies of the impact of development on the built environment often concentrate on areas of sudden change, where new constructions of a radically different scale, purpose or style are clearly seen to dramatically alter existing places. However, change is often more gradual. The cumulative effects of a large number of individual small changes are both extensive and often unrecognized until after they have taken effect, each individual development having 'slipped through the net' cast by planning authorities. The problem with this incremental process is that the result is often the erosion of the spatial and experiential qualities previously valued in that locality. As an example, this paper investigates four residential planning case studies in Queenscliff, a small historic coastal town in Victoria, Australia. Through analysis of their individual and cumulative impact on the neighbourhood character of this town, the paper explores the broader implications for the built environment of other Australian coastal towns and highlights the difficulties faced by all planners and residents trying to protect the character of their towns.